'When evil deeds have their permissive pass': broken windows in William Shakespeare's Measure for Measure. Issue 2 (3rd July 2017) - Wilson, Jeffrey R.
ABSTRACT: This essay considers some questions of crime, criminal justice and criminology in William Shakespeare's play Measure for Measure (1604). In this early-modern English play, Shakespeare dramatized issues of criminology and criminal justice that Americans George Kelling and James Wilson theorized nearly four centuries later in their famous essay 'Broken Windows' (1982). While this observation allows us to consider the possibility that Shakespeare was doing something like criminology centuries before there was an organized academic discipline called 'criminology', a close reading of Measure for Measure also allows us to identify some of the faulty thinking in broken windows policing. Specifically, Shakespeare's play shows the abuses of power that can occur when individual law enforcement agents receive both a mandate to crack down on social disorder and the authority to decide for themselves what counts as disorder and how to fight it. Thus, while social scientific research and public opinion have recently called broken windows policing into question, this approach to crime control was already discredited by William Shakespeare more than 400 years ago.